2013
DOI: 10.1111/bor.12017
|View full text |Cite
|
Sign up to set email alerts
|

Tree‐ring‐based annual precipitation reconstruction for the Hexi Corridor, NW China: consequences for climate history on and beyond the mid‐latitude Asian continent

Abstract: An annual (July to June) precipitation reconstruction for the period AD 1760–2010 was developed from a Picea crassifolia regional tree‐ring chronology from two sites in the northern mountainous region of the Hexi Corridor, NW China. This reconstruction explains 52.1% of the actual precipitation variance during the period 1951 to 2010. Spatial correlations with gridded land‐surface data reveal that our reconstruction contains a strong regional precipitation signal for the Hexi Corridor and for the southern marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 68 publications
3
21
1
Order By: Relevance
“…The water stress in summer was considered to play an important role in influencing radial growth. This seemed to be a common phenomenon for Picea crassifolia in the Qilian Mountains, because other studies in the study area obtained similar results where radial growth was significantly correlated with climatic factors in the previous July and August and the current June-August [25,[38][39][40].…”
Section: Different Response Of Radial Growth To Climate In the Differsupporting
confidence: 74%
“…The water stress in summer was considered to play an important role in influencing radial growth. This seemed to be a common phenomenon for Picea crassifolia in the Qilian Mountains, because other studies in the study area obtained similar results where radial growth was significantly correlated with climatic factors in the previous July and August and the current June-August [25,[38][39][40].…”
Section: Different Response Of Radial Growth To Climate In the Differsupporting
confidence: 74%
“…Of particular interest is the opposite trends during the 1910-1930s and the recent years. The drought events in the late 1920s (Pederson et al 2001;Liang et al 2003;Liu et al 2009;Chen et al 2011aChen et al , b, 2012Chen et al , 2013bChen et al , 2014c, as it has also been showed by this study. However, the impact of the drought on the Manasi River basin was relatively minor.…”
Section: Regional Comparisonsupporting
confidence: 86%
“…The authors of another study [76], show growing trend in yearly average standardized precipitationevapotranspiration index (SPEI) with a meaning change in 1986 and after, was justified by the current work. Figure 7b, the most significant area of correlation was found in the Indian Ocean [63,78], suggesting that SST of this ocean is an important factor affecting the growth of J. Turkestanica in Taboshar. Indian Ocean is the moisture source to our study area which fall into the Indian Monsoon domain as reported by a study [79].…”
Section: The Comparison Of Regional Recordsmentioning
confidence: 94%